2018
DOI: 10.2174/1389450117666161223125417
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine System and Multiple Sclerosis, Pathomechanism and Drug Targets with An Emphasis on Laquinimod

Abstract: Multiple sclerosis is a common chronic, disabling autoimmune neurological disease affecting mainly young adults. In its pathomechanism, neurodegenerative and acute inflammatory characteristics are both involved. Disease-modifying therapies aim to reduce relapse-rate and slow down the deterioration in neurological functions. The currently available therapies fail to exert neuroprotective effects and most of them are associated with potentially toxic side-effects, therefore, ongoing research aims to develop nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…The pathway is tightly regulated by enzymes and several of its metabolites are neuroactive with tissue- and cell-specific effects. 1 Activation of the kynurenine pathway is implicated in a variety of disorders and diseases, including tick-borne encephalitis (TBE), 2 human immunodeficiency virus infection (HIV), 2,3 malaria, 4,5 system lupus erythematosus (SLE), 6,7 multiple sclerosis (MS), 8,9 cardiovascular disorder, 10 and diabetes. 11-13 Furthermore, activation of the kynurenine pathway is present in psychiatric disorders such as schizophrenia, 14,15 major depression, 16 bipolar disorder, 17,18 and suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…The pathway is tightly regulated by enzymes and several of its metabolites are neuroactive with tissue- and cell-specific effects. 1 Activation of the kynurenine pathway is implicated in a variety of disorders and diseases, including tick-borne encephalitis (TBE), 2 human immunodeficiency virus infection (HIV), 2,3 malaria, 4,5 system lupus erythematosus (SLE), 6,7 multiple sclerosis (MS), 8,9 cardiovascular disorder, 10 and diabetes. 11-13 Furthermore, activation of the kynurenine pathway is present in psychiatric disorders such as schizophrenia, 14,15 major depression, 16 bipolar disorder, 17,18 and suicidality.…”
Section: Introductionmentioning
confidence: 99%
“…Estimations put its concentration in the CNS around 13% of the blood concentration [282]. It has a half-life of approximately 80 h and it is metabolized by cytochrome P450 (CYP 450) enzyme family [279].…”
Section: Laquinimodmentioning
confidence: 99%
“…It reduces the number of CD4 + dendritic cells and through it, the amount of Th1 and Th17 cells, while increasing the number of Treg cells [288]. Laquinimod was also shown to decrease microglial activation, leading to reduced axonal damage [279]. A recent study has concluded that laquinimod can induce remyelination through the protection of oligodendrocyte progenitors during differentiation [289].…”
Section: Laquinimodmentioning
confidence: 99%
See 2 more Smart Citations